2020
DOI: 10.1097/jom.0000000000002118
|View full text |Cite
|
Sign up to set email alerts
|

A Physician's Guide for Workers’ Return to Work During COVID-19 Pandemic

Abstract: Objective: Higher probability of developing severe COVID-19 has been associated with health risk factors and medical conditions which are common among workers globally. For at risk workers, return to work may require additional protective policies and procedures. Methods: A review of the medical literature was conducted on health risk factors and medical conditions associated with increased COVID-19 morbidity and mortality, standardized measures for community COVID tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 127 publications
(45 reference statements)
1
10
0
3
Order By: Relevance
“… * Without patient assistance: jobs that do not require contact patients (Baptista MC, et al, 2021 ). ** Non COVID care: assistance to patients without a diagnosis of COVID-19.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… * Without patient assistance: jobs that do not require contact patients (Baptista MC, et al, 2021 ). ** Non COVID care: assistance to patients without a diagnosis of COVID-19.…”
Section: Resultsmentioning
confidence: 99%
“… * Without patient assistance: jobs that do not require contact patients (Baptista MC, et al, 2021 ). …”
Section: Resultsmentioning
confidence: 99%
“…Similarly a report by Mutambudzi and coworkers reported an increased risk of severe COVID-19 for essential workers, with a risk ratio of 1.60 [ 20 ]. However, a limited number of studies observed topics specifically related to administrative, cleric, or municipal workers in the local public administration who are also exposed and of service to the public, and none of these studies estimated seroprevalence or risk among this group [ 33 , 34 ]. Fellows of the Collegium Ramazzini generally concluded that increased risk of COVID-19 infection is posed for workers with exposure and contact to infected persons and the public [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Diversas investigaciones han encontrado que existe un grupo de trabajadores que tienen condiciones de salud con mayor riesgo para desarrollar síntomas severos de la COVID-19 y, que, por lo tanto, están asociados a mayor morbilidad y mortalidad (3) . En una revisión de 10 metanálisis, concluyeron que había asociación significativa entre las complicaciones de la COVID-19 y la presencia de diabetes, enfermedades cardiovasculares, enfermedades respiratorias crónicas, edad avanzada, género varón, hábito de fumar, hipertensión, gestación y otras condiciones neurológicas (4) . Ante esta situación y en coherencia con los controles para proteger al huésped susceptible, el Gobierno peruano determinó que los trabajadores en el grupo de riesgo debían realizar trabajo remoto o teletrabajo (5) , al menos hasta que esté disponible la inmunización (4) .…”
Section: Sr Editorunclassified
“…La Administración de Seguridad y Salud Ocupacional (OSHA) de los EEUU, calificó los siguientes niveles: (i) nivel de muy alto riesgo, incluye al personal de salud asistencial y de laboratorio que realizan procedimientos con generación de bioaerosoles y trabajadores que trabajan con pacientes con COVID-19 en lugares cerrados y conglomerados sin ventilación adecuada; (ii) el nivel de alto riesgo, incluye al personal de salud asistencial o triaje, el personal que transporta pacientes, personal que realiza limpieza de ambientes asistenciales ocupados por pacientes casos de COVID-19 y los trabajadores que manipulan secreciones respiratorias, saliva o desechos de pacientes casos de COVID-19; (iii) el nivel de riesgo medio incluye al personal de salud que no puede guardar un distanciamiento de 2 metros de personas que podrían estar infectadas; y (iv) el bajo riesgo incluye a los trabajadores que realizan tareas administrativas que no requieren contacto menor a 2 metros con pacientes u otros trabajadores (4,8,10) . Sin embargo, los niveles de riesgo establecidos no consideraban eventuales controles que pudieran implementarse en el lugar de trabajo, teniendo en cuenta que para la prevención de riesgos laborales las…”
Section: Sr Editorunclassified